Rapid Quantification of Cell Viability and Apoptosis in B-Cell Lymphoma Cultures Using Cyanine SYTO Probes - Wlodkowic, Donald (2011)
The gross majority of classical apoptotic hallmarks can be rapidly examined by multiparameter flow cytometry. As a result, cytometry became a technology of choice in diverse studies of cellular demise. In this context, a novel class of substituted unsymmetrical cyanine SYTO probes has recently become commercially available. Derived from thiazole orange, SYTO display low intrinsic fluorescence, with strong enhancement upon binding to DNA and/or RNA. Broad selection of excitation/emission spectra has recently driven implementation of SYTO dyes in polychromatic protocols with the detection of apoptosis being one of the most prominent applications In this chapter, we outline a handful of commonly used protocols for the assessment of apoptotic events using selected SYTO probes (SYTO 16, 62, 80) in conjunction with common plasma membrane permeability markers (PI, YO-PRO 1, 7-AAD).